(untitled) (Journal of Experimental and Clinical Anatomy, 2024)
The influence of the aqueous crude extracts of Ocimum gratissimum Linn. leaf on cadmium (Cd)-induced toxic effects on spermatic parameters of the male guineapig (GP) was investigated. In n=5, Cd (0-8mg/kg) caused a dose-dependent inhibition or reduction of various spermatogenic parameters namely - number of normal sperm cells: 55.75±2.02 ×106 to 7.50±1.19 ×106 /ml; number of abnormal sperm cells: 2.25±0.25 ×106 to 8.25±2.18 ×106 /ml and total sperm count: 58.00±1.96 ×106 to 15.75±2.63 × 106 /ml; motility: 64.25±2.39 % to 26.50±1.71%; morphology: 5.75±0.75 % to 38.25±2.72 %; and a significant increase (P<0.05) in particulate and primordial sperm cell counts in the male GP. However, injection of Ocimum gratissimum Linn. extract after Cd administration had little or no significant effect on the above-mentioned parameters. Pretreatment with 5mg of O. gratissimum, with subsequent administration of cadmium, blocked or reversed the Cd-induced toxicities on the various spermatogenic parameters- motility:26.50±1.71% to 53.25±2.14%; morphology: 38.25±2.72% to 8.75±1.25%; number of normal sperm cells: 7.50±1.19 ×106 to 27.25±1.60 ×106 /ml; number of abnormal sperm cells: 8.25±2.18 ×106 to 5.25±0.63 ×106 /ml and total sperm count: 15.75±2.63×106 to 32.50±1.85 ×106 /ml. The observed influence of O. gratissimum on Cd-induced toxicity may be the consequence of the antioxidant action of the plant extract on the spermatogenic apparatus of the organism.